Three-phase four-wire shunt active power filter working simultaneously as energy conditioner. Issue 3 (2nd May 2017) - Szromba, Andrzej
Abstract : Purpose: The purpose of this study is to find a control method for three-phase four-wire shunt active power filters, which uses a load-equivalent conductance for obtaining a reference signal for compensating non-active current. Design/methodology/approach: Changes of energy stored in an active filter's reactance elements are monitored to find the active component of the load current. It is then used as a current reference to be realised as a supply source current. Computer simulation methods were used to verify the presented control method. Findings: To calculate the reference signal for the active filter action, it is enough to measure the active filter's DC-side capacitors' voltages. It has been proved that P regulators are sufficient to realise compensating current and to stabilise active filter capacitors' voltages. The supply source-neutral conductor current can be zeroed even for nonlinear and unbalanced load-generating DC-component in its neutral conductor. In addition, the active filter can buffer load-active power changes and act simultaneously as a local energy accumulator. Originality/value: This paper provides an alternative approach to address the problem of the three-phase four-wire shunt active power filter control methods.